Utilization Of Family Medicinal Plants (TOGA) In Health Improvement Efforts - Syaiful Bachri; Rahmat Pannyiwi; Sara Surya (International Journal of Health Sciences, 2026)
Family Medicinal Plants (TOGA) is a form of natural resource utilization that plays a role in public health promotion and prevention efforts. Utilization of TOGA can increase family independence in maintaining health and reduce dependence on synthetic drugs for minor complaints. This study aims to analyze the level of TOGA utilization and its impact on improving family health. The study used a descriptive analytical design with a cross-sectional approach. The study sample consisted of 60 heads of families who have TOGA plants in region X. Data were collected through questionnaires and direct observation. The results showed that 75% of respondents utilized TOGA for minor complaints such as coughs, fevers, and digestive disorders. Utilization of TOGA is associated with increased healthy living behavior and decreased use of chemical drugs for minor complaints (p < 0.05). It is concluded that TOGA plays an important role in supporting efforts to improve family health.